2011
DOI: 10.5402/2011/868356
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Surgical Treatment in Late-Diagnosed Esophageal Perforation: A Report of 11 Cases

Abstract: Introduction. Esophageal perforation is a relatively uncommon and lethal disease usually resulting from endoscopic procedures. Delay in the diagnosis and treatment occurs in more than 50% of cases, leading to a mortality rate of 40% to 60%, but this rate decreases is 10%–25% if treatment is carried out within 24 hours of perforation. Case Presentation. To analyze the characteristics, etiology, site of perforation, presentation, time interval till diagnosis, treatment and outcome of patients with esophageal per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…In recent decades, endoscopic examination of digestive organs and transesophageal echography for cardiovascular disease evaluation have had great impacts on the early detection and improved the outcomes of digestive system and heart diseases [ 14 ]. However, the incidence of iatrogenic esophageal perforation as assessed using endoscopic examinations has also increased in proportion to the incidence of EPR [ 2 , 15 ]. Recent studies have suggested that iatrogenic causes are the most common etiology of EPR [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, endoscopic examination of digestive organs and transesophageal echography for cardiovascular disease evaluation have had great impacts on the early detection and improved the outcomes of digestive system and heart diseases [ 14 ]. However, the incidence of iatrogenic esophageal perforation as assessed using endoscopic examinations has also increased in proportion to the incidence of EPR [ 2 , 15 ]. Recent studies have suggested that iatrogenic causes are the most common etiology of EPR [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, endoscopic examination of digestive organs and transesophageal echography for cardiovascular disease evaluation have had great impacts on the early detection and improved the outcomes of digestive system and heart diseases [14]. However, the incidence of iatrogenic esophageal perforation as assessed using endoscopic examinations has also increased in proportion to the incidence of EPR [2,15]. Recent studies have suggested that iatrogenic causes are the most common etiology of EPR [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…First, it can usually be diagnosed rapidly. The main reason for EPR treatment failure is delayed diagnosis and intervention [15,18]. This is because the symptoms of EPR are usually nonspeci c, such as chest discomfort, orthopnea, fever, and dysphagia [8,19,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…More than 50% of esophageal perforation were delayed in diagnosis and therapy [5]. The main reason for the delay in diagnosis of this patient is that her neck injury and infection is not obvious.…”
Section: Discussionmentioning
confidence: 99%